A Decade of mTBI Experience: What Have We Learned? A Summary of Proceedings From a NATO Lecture Series on Military mTBI - Robinson-Freeman, Katherine E.; Collins, Kassondra L.; Garber, Bryan; Terblanche, Ronel; Risling, Marten; Vermetten, Eric; Besemann, Markus; Mistlin, Alan; Tsao, Jack W. (Frontiers in Neurology, 2020)
Mild traumatic brain injury (mTBI, also known as a concussion) as a consequence of battlefield blast exposure or blunt force trauma has been of increasing concern to militaries during recent conflicts. This concern is due to the frequency of exposure to improvised explosive devices for forces engaged in operations both in Iraq and Afghanistan coupled with the recognition that mTBI may go unreported or undetected. Blasts can lead to mTBI through a variety of mechanisms. Debate continues as to whether exposure to a primary blast wave alone is sufficient to create brain injury in humans, and if so, exactly how this occurs with an intact skull. Resources dedicated to research in this area have also varied substantially among contributing NATO countries. Most of the research has been conducted in the US, focused on addressing uncertainties in management practices. Development of objective diagnostic tests should be a top priority to facilitate both diagnosis and prognosis, thereby improving management. It is expected that blast exposure and blunt force trauma to the head will continue to be a potential source of injury during future conflicts. An improved understanding of the effects of blast exposure will better enable military medical providers to manage mTBI cases and develop optimal protective measures. Without the immediate pressures that come with a high operational tempo, the time is right to look back at lessons learned, make full use of available data, and modify mitigation strategies with both available evidence and new evidence as it comes to light. Towards that end, leveraging our cooperation with the civilian medical community is critical because the military experience over the past ten years has led to a renewed interest in many similar issues pertaining to mTBI in the civilian world. Such cross-fertilization of knowledge will undoubtedly benefit all. This paper highlights similarities and differences in approach to mTBI patient care in NATO and partner countries and provides a summary of and lessons learned from a NATO lecture series on the topic of mTBI, demonstrating utility of having patients present their experiences to a medical audience, linking practical clinical care to policy approaches.